Religion, politics and war: Recollections on General Ndaya and Kenya’s quest for independence - Julius M. Gathogo (Theologia Viatorum, 2024)
The mosaic law of advocating the paying of life with life, and an “eye for eye, tooth for tooth, hand for hand, foot for foot, burn for burn, wound for wound, [and] stripe for stripe” (Exodus 21:23-25), came out clearly on 15th and 16th October 1953, as the politics of land and freedom [wiyathi na ithaka] in the colonial Kenya brought their ugly faces through a deadly violence. While the 15th October saw the Mau Mau rebels attack and kill two Roman Catholic Sisters (Cecilia Wangeci and Rosetta Njeri) at the Baricho Centre, the 16th October 1953 saw the capture of the rebel’s leader (Wanjagi wa Ndegwa, also known as General Ndaya) and his subsequent killing. In trying to understand the interface between religion, politics, and war in the African context, the research article has sampled the twin issues (the battle of River Ragati and the attacks on the Baricho Catholic Church of 1953)to alert the post-colonial Africa on the dangers of conflict among the trio.